2017
DOI: 10.1021/acs.jchemed.7b00397
|View full text |Cite
|
Sign up to set email alerts
|

Reforming a Large Foundational Course: Successes and Challenges

Abstract: The Information Technology and Innovation Foundation (ITIF) is a Washington, D.C.-based think tank at the cutting edge of designing innovation policies and exploring how advances in information technology will create new economic opportunities to improve the quality of life. Nonprofit, and nonpartisan, ITIF offers pragmatic ideas that break free of economic philosophies born in eras long before the first punch card computer and well before the rise of modern China. ITIF, founded in 2006, is dedicated to concei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 61 publications
0
68
0
1
Order By: Relevance
“…Five studies (Eichler & Peeples, ; He, ; Lewis, ; Robert et al, ; Tien, Roth, & Kampmeier, ) used peer leaders or teaching assistants to facilitate interactions within large classes. Of the remaining three studies, two reported class sizes of approximately 100 students (Baepler et al, ; Casadonte, ) and the remaining study (Talanquer & Pollard, ) a class size of 250 students. Two (He, ; Talanquer & Pollard, ) of the eight studies make explicit mention of the challenges in implementation with a large class describing difficulties in ensuring student preparation, promoting student engagement and providing feedback on misconceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (Eichler & Peeples, ; He, ; Lewis, ; Robert et al, ; Tien, Roth, & Kampmeier, ) used peer leaders or teaching assistants to facilitate interactions within large classes. Of the remaining three studies, two reported class sizes of approximately 100 students (Baepler et al, ; Casadonte, ) and the remaining study (Talanquer & Pollard, ) a class size of 250 students. Two (He, ; Talanquer & Pollard, ) of the eight studies make explicit mention of the challenges in implementation with a large class describing difficulties in ensuring student preparation, promoting student engagement and providing feedback on misconceptions.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining three studies, two reported class sizes of approximately 100 students (Baepler et al, ; Casadonte, ) and the remaining study (Talanquer & Pollard, ) a class size of 250 students. Two (He, ; Talanquer & Pollard, ) of the eight studies make explicit mention of the challenges in implementation with a large class describing difficulties in ensuring student preparation, promoting student engagement and providing feedback on misconceptions. It is also noted that He () was the only study of the five with teaching assistants to not mention the number of assistants present.…”
Section: Resultsmentioning
confidence: 99%
“…Science curricula that are structured by surface features do not provide opportunities to connect concepts and build expert‐like understanding (Cooper & Stowe, ). Internationally, efforts are being made toward curricular reform, especially in high school and general chemistry (Cooper & Klymkowsky, ; National Research Council, ; Sevian & Talanquer, ; Talanquer & Pollard, , ). In organic chemistry, curricula have historically been reorganized by surface features (i.e., functional groups) and assessments have rarely asked students to make mechanistic connections across a variety of reaction types.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that students who struggled with these foundational aspects of the problem do so because of a lack of well‐developed schemas . One potential way to help students construct organized schemas is through conceptual curriculum design such as POGIL , Chemical Thinking , or CLUE Chemistry . Each of these approaches thoughtfully scaffolds disciplinary knowledge in a meaningful progression, which can contribute to dramatic improvements in conceptual understanding .…”
Section: Discussionmentioning
confidence: 99%